SISTEM PENERJEMAH INGGRIS-INDONESIA PADA APLIKASI CHATTING BERBASIS WEB MENGGUNAKAN PENDEKATAN ATURAN - Muhammad Syaukani (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
The using of chatting application among Indonesian people continues to rise on strong demand. Unfortunately, the language problems arise when chat with strangers. This research focuses on the development of online communication system using the translator of English and Indonesian. This system is designed for communication media chat application that can translate messages sent from user to other users. This system provides an alternative solution for those who experienced difficulties in communicating with people of different languages and it was developed from previous research.  The web-based chat applications systems is developed using PHP programming language, and the translator application is developed using rule-based approach, i.e. parsing tree concept and production rules. In this researach, the testing of system is conducted by sending a message in English sentences and the received message in Indonesian sentences and vice-versa. The results show that the system has successfully sent messages from sender to recipient.